Action of Actomyosin Contraction With Shh Modulation Drive Epithelial Folding in the Circumvallate Papilla - Zhang, Sushan; Lee, Jong-Min; Ashok, Adpaikar Anish; Jung, Han-Sung (Frontiers in Physiology, 2020)
The mouse tongue possesses three types of gustatory papillae: large circumvallate papillae (CVP), foliate papillae (FOP) and fungiform papillae (FFP). Although CVP is the largest papilla and contain a high density of taste buds, little is known about CVP development. Their transition from placode to dome-shape is particularly ambiguous. Understanding this phase is crucial since dome-shaped morphology is essential for proper localization of the imminent nerve fibers and taste buds. Here, we report actomyosin-dependent apical and basal constriction of epithelial cells during dynamic epithelial folding. Furthermore, actomyosin-dependent basal constriction requires focal adhesion kinase to guide dome-shape formation. Sonic hedgehog (Shh) is closely associated with the migration of neuroblasts and cytoskeletal alteration in trench epithelial cells which regulate CVP morphogenesis. Our results demonstrate the CVP morphogenesis mechanism from placode to dome-shape by actomyosin-dependent cell shape change and suggest roles that Shh may play in trench and stromal core formation during CVP development.